Methodology of organizing and conducting pedagogical experimenttesting in the environment of digital training of professional education - Ro'ziyev Dilshod Ubaydulayevich (Genius Journals, 2024)
This article development of students' readiness for independent educational activities in the digital training environment of professional education model, provided pedagogical conditions, mechanism, improved methodology and effectiveness of pedagogical technology in the process of pedagogical experiment-testing are presented.
Keywords: Pedagogical conditions; pedagogical process; digital education